UJI AKTIVITAS ANTIBAKTERI DARI ISOLAT CENDAWAN ENDOFIT ASAL TUMBUHAN SENDUDUK (Melastoma malabathricum L.) TERHADAP Escherichia coli DAN Staphylococcus aureus - Harahap, Israwati; Rahmi, Vivin Paddillah; Herlina, Nofripa (Sistem Informasi, 2018)
Endophytic fungi is a symbiotic microorganism which live inside plant tissues and not harm to their host. Several genera from endophytic fungi known to produce secondary metabolite compounds like antibiotics, anticancer, antifungal, antiviral and antimalarial. This study aimed to investigate antibacterial activity of endophytic fungi from senduduk (Melastoma malabathricum L.) against Escherichia coli and Staphylococcus aureus. Based on the test result, 11 isolates endophytic fungi from senduduk were known to have antibacterial activities. Isolate code 23 have ability to inhibit the growth of E.coli with diameters zone of inhibition is 22 mm and eight isolate endophytic fungi have ability to inhibit the growth of S.aureus (showed by inhibition zone).